2002
DOI: 10.1021/ol0266471
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Esterification of Phenolic Acids and Alcohols

Abstract: [formula: see text] The Mitsunobu reaction can distinguish between alcohol and phenol hydroxyls in esterification reactions, providing an expeditious and broadly applicable entry into various phenolics and polyphenolics of biomedical and nutritional relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…General Synthetic Procedure for Polyphenolic Acid Ester Derivatives The esters were synthesized from polyphenolic acid and 2-phenoxy ethanol by Mitsunobu esterification using DIAD and TPP as coupling reagents 28) as shown in Fig. 1.…”
mentioning
confidence: 99%
“…General Synthetic Procedure for Polyphenolic Acid Ester Derivatives The esters were synthesized from polyphenolic acid and 2-phenoxy ethanol by Mitsunobu esterification using DIAD and TPP as coupling reagents 28) as shown in Fig. 1.…”
mentioning
confidence: 99%
“…Under basic catalysis, phenols can be easily deprotonated, so the esterification of phenolic alcohols and phenolic acids via acyl nucleophilic substitution requires previous protection of the phenolic hydroxyl groups, due to the competition between aliphatic and phenolic hydroxyl groups (Appendino et al, 2002;Gambacorta et al, 2007).…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…Synthesis of hydroxytyrosyl acetate via benzylation of phenolic hydroxyls A two-step procedure involving the reaction of methyl orthoformate-protected hydroxytyrosol with acetyl chloride, and hydrolytic deprotection in phosphate buffer under very mild conditions (pH=7.2) to get hydroxytyrosyl acetate (87% overall yield) (Scheme 3) was also described as a successful procedure for the preparation of HT-derived esters (Gambacorta et al, 2007 In order to overcome the problems associated to the protection and deprotection steps of the phenolic hydroxyl groups, different methods for the preparation of hydroxytyrosyl esters by reaction of hydroxytyrosol with various acylating agents have been described, such as esterification with free acids (Appendino et al, 2002), transesterification with methyl or ethyl esters (Alcudia et al, 2004;Trujillo et al, 2006), acyl chlorides (Torregiani et al, 2005) and the use of enzymatic methodologies (Grasso et al, 2007;Mateos et al, 2008;Torres de Pinedo et al, 2005;Buisman, 1998).…”
Section: Protection Of Phenolic Hydroxyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the synthesis via acid chloride was straightforward, a one-step esterification in which acids react directly with alcohol is practical because of the troublesome protection and deprotection steps. The recent study by Appenedino et al 26) indicated that the Mitsunobu reaction is especially suitable for the esterification of phenolic acids and alcohols. Because phenolic carbons are not substrates for the SN2-type reaction, the Mitsunobu reaction shows good chemoselectivity between hydroxyl groups bound to aliphatic and aromatic carbons.…”
Section: Synthesis Of Selenium-containing Polyphenolic Acid Esters Anmentioning
confidence: 99%